Non-bone metastatic cancers promote osteocyte-induced bone destruction. (1st November 2021) - Pin, Fabrizio; Prideaux, Matthew; Huot, Joshua R.; Essex, Alyson L.; Plotkin, Lilian I.; Bonetto, Andrea; Bonewald, Lynda F.
Abstract: The effects of bone metastatic cancer on the skeleton are well described, whereas less is known regarding the effects of non-metastatic bone cancer on bone. Here we investigated the effects of three non-bone metastatic cancer cachexia models, namely Colon-26 adenocarcinoma (C26), ES-2 ovarian cancer (ES-2), and Lewis lung carcinoma (LLC). Even though C26, ES-2 and LLC tumor growth resulted in comparable weight and muscle loss, the ES-2 and LLC hosts exhibited severe bone loss, whereas only modest bone loss was observed in the C26 bearers, correlating with increased TRAP + osteoclasts in the femurs of ES-2 and LLC but not C26 hosts. Surprisingly, all three showed increased osteocyte lacunar area indicating osteocytic osteolysis and displayed dramatically increased osteocyte death, as well as empty lacunae. To test whether tumor-secreted factors were responsible for the observed effect, IDG-SW3 osteocyte cells were co-cultured with cancer cells in permeable trans -wells. Apoptosis was observed in the osteocyte cells exposed to all three cancer cell lines suggesting that all tumors were cytotoxic for osteocytes. In addition, the expression of the osteoclastic markers, Acp5, CtsK, Atp6v0d2 and Mmp13, was elevated in IDG-SW3 osteocytes exposed to tumor factors, supporting the in vivo observations of increased lacunar size due to osteocytic osteolysis. For the first time, we describe osteocytic bone destruction and extensive osteocyte cell death in non-bone metastatic cancer. These bone alterations, in conjunction with muscle wasting, may create a musculoskeletal system that is incapable of full recovery upon eradication of tumor. Co-treatment with bone preserving therapies should be considered.